Shear strength analysis of concrete beams reinforced with GFRP bars using strut and tie model - Mokhtar, Norfaniza (2011)
This dissertation presents an experimental investigation on the behavior and ultimate shear strength of reinforced concrete beam. Sixteen reinforced concrete beams was design and tested to failure. This study consists of two series of beams, which are conventional steel reinforced beams (BSN) and reinforced concrete beams with Strut and Tie Model (STM) using StaadPro software and both result were compared in term of shear strength. The main test variables were shear span-to-depth ratio (2.1 and 2.9), percent of longitudinal reinforcement ratio (tension) steel and GFRP (0.6% and 0.9%), and shear reinforcement ratio (1.5% and 0.6%). The test results revealed that the mode of failure for all beam is flexural with shear reinforcement characteristics and longitudinal reinforcement ratio play a critical role in controlling the mode of failure. The experimental approved that the spacing between shear cracks for the specimens with larger shear span to depth ratio is greater than the smaller shear span to depth ratio and while the shear span to depth ratio (a/d) decreases, the shear strength increase. For longitudinal reinforcement ratio it can be inferred that the higher longitudinal reinforcement ratio brings the smaller diagonal crack. Also, greater stirrup spacing leads to the greater diagonal crack, confirming that there is a significant influence of the stirrup spacing on the spacing between shear cracks. The reason for this behavior is the decreasing effective concrete area, in which shear crack width is controlled by the stirrup, and hence the increasing bond effect between the stirrup and the surrounding concrete.